2021
DOI: 10.3390/ph14030276
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Manifestations in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease characterized by a wide spectrum of clinical manifestations. The respiratory system can be involved in up to 50–70% of patients and be the presenting manifestation of the disease in 4–5% of cases. Every part of the respiratory part can be involved, and the severity can vary from mild self-limiting to life threatening forms. Respiratory involvement can be primary (caused by SLE itself) or secondary (e.g., infections or drug toxicity), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 140 publications
(336 reference statements)
0
19
0
3
Order By: Relevance
“…As a chronic and systemic autoimmune disease, SLE is characterized by the dysfunction of immune cells, the production of a wide range of autoantibodies and the formation of immune complexes ( 51 , 52 ). It was reported that dihydroartemisinin suppressed LPS-induced activation and proliferation of spleen cells from lupus-prone MRL/lpr mice possibly through inhibiting TLR4 expression and IRF3 phosphorylation ( 53 ).…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…As a chronic and systemic autoimmune disease, SLE is characterized by the dysfunction of immune cells, the production of a wide range of autoantibodies and the formation of immune complexes ( 51 , 52 ). It was reported that dihydroartemisinin suppressed LPS-induced activation and proliferation of spleen cells from lupus-prone MRL/lpr mice possibly through inhibiting TLR4 expression and IRF3 phosphorylation ( 53 ).…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“… 18 Advanced age, presence of massive hemoptysis, need for mechanical ventilation, previous plasmapheresis treatment, presence of thrombocytopenia, as well as infections have been associated with higher mortality risk. 4 Alveolar hemorrhage secondary to SLE is more common in young women, 19 as it was in this case. The following etiologies must be considered in the presence of alveolar hemorrhage: primary capillaritis (e.g., microscopic polyangiitis, ANCA-associated vasculitis, granulomatosis with polyangiitis, eosinophilic granulomatosis with polyangiitis, isolated pauci-immune pulmonary capillaritis, and Henoch–Schönlein purpura) and without capillaritis (e.g., SLE, scleroderma, primary anti-phospholipid syndrome, polymyositis, rheumatoid arthritis, mixed connective tissue disease, drug-induced vasculitis, IgA nephropathy, and anti-glomerular basement membrane antibody disease).…”
Section: Discussionmentioning
confidence: 54%
“…The radiological patterns suggestive of alveolar hemorrhage can be present 48–72 h after the clinical onset. 4 SLE patients who present alveolar hemorrhage have approximately a 50% mortality rate. 18 Advanced age, presence of massive hemoptysis, need for mechanical ventilation, previous plasmapheresis treatment, presence of thrombocytopenia, as well as infections have been associated with higher mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Although a reduced DLCO is commonly interpreted as a sign of interstitial pathology impairing diffusion across from the alveoli to the blood, it can occur in the absence of interstitial pathology. In SLS, a reduced DLCO is attributed to the decreased effective alveolar surface area caused by the lower lung volumes; it can also be attributed to consequential pulmonary hypertension and alveolar surfactant dysregulation [ 11 - 12 ].…”
Section: Discussionmentioning
confidence: 99%